HUBUNGAN STATUS GIZI DENGAN TEKANAN DARAH PADA SISWA SEKOLAH MENENGAH PERTAMA NEGERI 1 KOTA BITUNG - Andalangi, Jenifer; Warouw, Sarah M.; Umboh, Adrian (Universitas Sam Ratulangi, 2013)
Abstract: According to Riskesdas in 2010, the prevalences of nutritional status based on BMI at age group 13-15 in North Sulawesi were 0.7% very skinny; 5.3% thin; 90, 5% normal; and 3.4% obese. In Indonesia, the incidences of hypertension in adolescents varies from 3.11% to 4.6%. BMI has a strong relationship with blood pressure; BMI >95th percentile was strongly associated with increased blood pressure >90th percentile. This study aimed to determine the relationship of the nutritional status and blood pressure. The study was conducted in SMPN 1 Bitung. This was an analytic obsevational study with a cross-sectional design. Samples were 105 students aged 11-14 years, obtained by using simple random sampling. The nutritional status was defined as independent variables and the blood pressure as the dependent variable. Data were analyzed by using a chi-square test. The results showed that the nutritional status of students were underweight 10.5%, normal 71.4%, overweight 13.3%, and obese 4.8%. The normal blood pressure were found in 89.5%; high normal blood pressure 8.6%; and hypertension 1.9%. The chi-square test results showed a significant relationship between the nutritional status and the blood pressure (P = 0.001). Conclusion: There was a significant relationship between the nutritional status and the blood pressure among the junior high school students in Bitung. Keywords: blood pressure; nutritional status. Abstrak: Berdasarkan laporan Riskesdas tahun 2010, prevalensi status gizi berdasarkan IMT pada kelompok usia 13-15 tahun di Provinsi Sulawesi Utara menunjukkan angka 0,7% sangat kurus, 5,3% kurus, 90,5% normal, dan 3,4% gemuk. Di Indonesia, angka kejadian hipertensi pada remaja bervariasi dari 3,11% sampai 4,6%. IMT mempunyai hubungan yang kuat dengan tekanan darah, yaitu IMT >persentil 95 berhubungan kuat dengan peningkatan tekanan darah >persentil 90. Penelitian ini bertujuan untuk mengetahui hubungan status gizi dan tekanan darah. Penelitian dilakukan di SMP N 1 Bitung. Penelitian ini menggunakan metode survei analitik observasional dengan desain potong lintang, dengan jumlah sampel 105 siswa berusia 11-14 tahun, yang diambil dengan simple random sampling. Status gizi ditetapkan sebagai variabel independen dan tekanan darah sebagai variabel dependen. Uji statistik yang digunakan ialah chi-square. Untuk status gizi di dapat underweight 10,5%, normal 71,4%, overweight 13,3%, dan obes 4,8%. Untuk tekanan darah didapatkan tekanan darah normal 89,5%, normal tinggi 8,6%, dan hipertensi 1,9%. Hasil uji chi-square menyatakan adanya hubungan bermakna antara status gizi dan tekanan darah (P = 0,001). Simpulan: Terdapat hubungan bermakna antara status gizi dan tekanan darah. Kata kunci: status gizi, tekanan darah.